Geogrid pullout behaviour according to the experimental evaluation of the active length. Issue 3 (21st December 2015) - Cardile, G.; Moraci, N.; Calvarano, L. S.
Abstract : In reinforced earth structures, the main function of the included reinforcement is to redistribute stresses within the soil mass in order to enhance internal stability. Redistribution of internal stresses in reinforced soil can be very complex. In order to simulate the behaviour of geosynthetic reinforcement, large-scale laboratory pullout tests are carried out. Once a pullout load has been applied, the tensile force is transferred along the geogrid (from the front to the free end) and reduced through interaction with the soil. The active length is the portion of the geogrid on which the mobilisation of interaction mechanisms withstands the applied pullout load. Evaluation of the active length can allow for the understanding of the interaction mechanisms and can therefore be important for the design of the soil–geosynthetic interface. This paper describes the interpretation of pullout test results based on an experimental and theoretical evaluation of the active length. This approach has been used to analyse several large-scale pullout tests performed on two extruded geogrids embedded in a compacted granular soil, varying the specimen lengths and the applied effective vertical pressures.